NILAI MORAL TOKOH SATYA DALAM NOVEL SABTU BERSAMA BAPAK KARYA ADHITYA MULYA - Wiwik Surya Utami (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
Literary work is the result of the creation of the author or writer to be enjoyed and understood in the social life of society. The researcher chose the novel Saturday Together with Mr. Adhitya Mulya, a novel that has many moral values, this novel has 4 main characters, namely Mr. Gunawan Granida, Mrs. Itje, Satya and Cakra. This study only focuses on the character Satya, the eldest son of Pak Gunawan Granida. The purpose of this study was to describe the moral values of the Satya character in the novel Saturday Together with Mr. This research is a qualitative descriptive study using the method of listening and noting. The results of this study contained 5 moral aspects of human relations with oneself, namely morally responsible behavior, patience, controlling emotions, working hard, regret and admitting mistakes (apologies). Then, there are 3 moral aspects of human relations with other humans in the social and natural environment. Satya exhibits compassionate, caring and caring moral behavior. And in one aspect of the relationship between humans and God, there is not much moral behavior that leads to the relationship between humans and God, only shown in Satya's attitude to remind his children to worship.